Karakteristik Fonem Segmental Bahasa Melayu Dialek Ambon - Erniati Erniati (Kantor Bahasa Provinsi Maluku Utara, 2017)
Ambonese Malay is classified as a dialect of the standard Malay language spoken in Maluku Province including Ambon City, Ambon Island, Lease islands of Saparua, Haruku and Nusa Laut and Buano Island, Manipa Island, Kelang island, Seram island. In addition, this language is also used as a trading language in Kei, Banda, Watubela Islands, Buru Island, Southeast Maluku to Southwest Maluku. Ambonese Malay has 2-2.5 million speakers spreading throughout the Maluku Islands. Ambonese Malay is included in the Malay Polynesian family. To preserve Ambonese Malay, it is necessary to study the characteristics of phonemes of Ambonese Malay and its distribution in word. This study aims to determine the number of Ambonese Malay’s phonemes and its distribution in the word. The method used is descriptive qualitative method. The results show that the phoneme contained in Ambonese Malay consists of eighteen consonant phonemes.